TRANSMUTED NEW WEIGHTED EXPONENTIAL DISTRIBUTION: ITS DISTRIBUTIONAL PROPERTIES AND APPLICATIONS TO DATASETS FROM RAINFALL AND BREAST CANCER STUDIES - Abdullahi, Umar Kabir; Muhammed, Badawi Aminu; Inuwa, Ibrahim Yusuf; Garba, Jamilu; Adamu, Saudat Ali; Musa, Tasi’u; Falgore, Jamilu Yunusa (FUDMA JOURNAL OF SCIENCES, 2024)
This research paper developed a new distribution referred as transmuted Newweighted exponential distribution. This is an extension of the popular Exponential distribution by using the transmutation map, the probability density function (pdf) and the cumulative distribution function (cdf) of the developed distribution were derived. Some distributional properties of the new distribution were extensively studied. The estimation of the distribution parameters was done using the method of maximum likelihood estimation. The performance of the TNWED has been evaluated using real life datasets from two (2) previous researches and the results show that our proposed distribution fits the datasets more better compared to the fits of the other two distributions (New Weighted Exponential distribution and Exponential distribution) considered in this study.
Keywords: Distribution; Estimation; Likelihood; Transmuted; Weighted-Exponential